2007
DOI: 10.1098/rsbl.2007.0149
|View full text |Cite
|
Sign up to set email alerts
|

Psychological benefits of greenspace increase with biodiversity

Abstract: The world's human population is becoming concentrated into cities, giving rise to concerns that it is becoming increasingly isolated from nature. Urban public greenspaces form the arena of many people's daily contact with nature and such contact has measurable physical and psychological benefits. Here we show that these psychological benefits increase with the species richness of urban greenspaces. Moreover, we demonstrate that greenspace users can more or less accurately perceive species richness depending on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
797
8
33

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,226 publications
(869 citation statements)
references
References 15 publications
31
797
8
33
Order By: Relevance
“…This is validated by respondents stating that their spiritual experience would not be enhanced if the garden was larger, had a greater variety of plants, or contained certain tree species or amenities. This is contradictory to other studies illustrating that benefits received from urban green spaces increased with increasing area [11,62]. This maybe a consequence of most of the gardens in our sample being quite small (the largest being 0.5 ha).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is validated by respondents stating that their spiritual experience would not be enhanced if the garden was larger, had a greater variety of plants, or contained certain tree species or amenities. This is contradictory to other studies illustrating that benefits received from urban green spaces increased with increasing area [11,62]. This maybe a consequence of most of the gardens in our sample being quite small (the largest being 0.5 ha).…”
Section: Discussioncontrasting
confidence: 99%
“…The positive relationship of aesthetic appreciation and greenness reflects much other literature in which respondents express an affinity for green spaces [60,61]. The relationship with species richness has rarely been examined other than the seminal work of Fuller et al [62], who showed respondents' ranking of their feeling of distinct identity and to reflect increased in urban parks with increasing species richness.…”
Section: Discussionmentioning
confidence: 89%
“…It has been shown that the psychological benefits that humans gain from encountering urban greenspaces increase with the species richness of these greenspaces (Fuller et al, 2007). The medians in New York (and we suspect similar patches of habitat in other megacities) are sufficiently extreme to reduce diversity, even of disturbance-tolerant taxa such as ants.…”
Section: Discussionmentioning
confidence: 78%
“…De manera directa, un humedal con mayor diversidad de plantas o mayores índices de naturalidad, generaría mayores benefi cios desde el punto de vista de los servicios ecosistémicos de recreación y bienestar psicológico de la comunidad. Diversos estudios han mostrado correlaciones positivas entre el grado de naturalidad de áreas verdes urbanas con variables de bienestar humano (Irvine et al, 2010), y en algunos casos han correlacionado incluso la riqueza de plantas, positivamente con variables psicológicas del bienestar y motivación para visitar áreas verdes urbanas (Dallimer et al, 2012, Fuller et al, 2007.…”
Section: Discusión Y Conclusiónunclassified